Industrial training report: Pejabat Pendidikan Daerah Kota Bharu / Mohammad Syaqir M Rusli - M Rusli, Mohammad Syaqir (Perpustakaan Tengku Anis, 2018)
This special project based on the period from 1st February 2018 until 30th June 2018 in Information and Technology (ICT) at PPD Kota Bharu. The trainee is placed in Unit ICt under the supervision of Mr. Faizal bin MD Noor which is a Penyelia ICT. The trainee is assigned to develop a corporate video as the special project which is PPDKB Corporate Video. Basically the PPDKB Corporate Video is being considered in order to show all the staff and visitor from outside to know information about PPDKB. Before this, PPDKB doesn't have any corporate video. However, the trainee also involved with other activities and programs which each of them gave new experience and gained a lot of knowledge. Throughout the industrial training session, the trainee had improved a lot of skills such as communication skill, problem solving, self- learning, teamwork and others. The industrial training session are going well until the end of the day. The staff in Pejabat Pendidikan Daerah Kota Bharu (PPDKB) gave a very good cooperation with the trainee during the industrial training session.